QUARNEWSS: a model for applying Six Sigma framework to achieve continuous quality and reliability improvement in new product development. (27th December 2010) - Natarajan, M.; Senthil, V.; Devadasan, S.R.; Vijay Mohan, N.
Of late, new product development (NPD) and application of Six Sigma are actively pursued in organisations. Yet there has been no report of implementing Six Sigma for achieving quality and reliability improvement in NPD. To overcome this deficiency, in this paper, a model named as QUARNEWSS has been contributed. This model has been developed after critically studying the researches reported in literature surmounting NPD, total quality management (TQM), Six Sigma and reliability arenas. In this model, four techniques and tools which are commonly applied in these arenas have formed as the core. After that, QUARNEWSS model has been incorporated with Six Sigma's define, measure, analyse, improve and control (DMAIC) improvement methodology and belt-based training infrastructure with four stages of NPD namely initialisation, conceptulation, prototyping and evolution. The working of QUARNEWSS model is illustrated by presenting a hypothetical case study.